Dieta, composição química, contaminação por metais pesados e análise sensorial do peixe matrinxã (Brycon falcatus, Müller & Troschel, 1844) em rios amazônicos - Matos, Liliane Stedile de (2014)
The Teles Pires River is suffering great pressure to fisheries resources, and the bait (food that is put in place to attract certain fish stocks) is being used by fishermen. In addition, there is the discharge of effluents from tanneries and discharge of pesticides to soil leaching in this water body. Hence, the objective of this study was to describe the diet, to determine the chemical composition, contamination by Copper and Chromium and analyze the flavor and color of the fillet matrinxã in the Teles Pires river basin, in places with no bait and bait in order to provide data for the management and control of potential supply of supplemental food (bait) in this basin. Catches was used for conventional fishing gear, the following points classified by density baits: Tapaiuna river (without cevas), Verde river (low ~ 1ceva/1000m), Celeste river (average ~ 1 ceva/500m) stretch on the Teles Pires river termed as Missioneira (high ceva/100m ~ 1) and Cristalino river (Conservation Unit / control), from July 2012 to July 2013. In UFMT (Biological Collection Southern Amazon ABAM) lab, for every sample data were obtained: Total length (TL), standard length (SL), total weight (TW), stages of repletion (ERE) and fat weight celomatic (PGC). The stomach content was analyzed using the method of frequency of occurrence, relative volume and feed rate. For the chemical composition were determined moisture, ash, protein, and fat. For analysis of Chromium and Copper digestion was performed with nitric acid and hydrogen peroxide by wet in triplicate. To evaluate the effects of baiting flavor of fillets matrinxã triangular test was applied to determine the color and the filet, the modified colorimetric method abanito Salmofan© was used. In Cristalino river matrinxã presented a diet with 16 items, the most important item was IAi = 9,528 sheets. In Teles Pires river in the stretch Missioneira the diet was composed of 11 items, the most important item was soy in nature with IAi = 88.253. The fillets matrinxãs coming Cristalino river had the lowest percentage of crude protein 17.81% which significantly differed from the other rivers. The fillets Brycon falcatus the Missioneira had the highest percentage of fat with 3.63%, differing significantly from Cristalino river, which showed 1.51% fat. In the analysis of heavy metals, chromium in the liver, the largest concentrations of fish were collected in the Missioneira with 2.48 μg.g ¯ ¹. Copper in the liver were higher in fish from the river with 62.70 Lens μg.g ¯ ¹, and Copper in the muscle samples of fish collected in Cristalino, Tapaiuna, Verde, Celeste and Missioneira rivers showed similar concentrations, ranging from 0.27 to 0.35 μg.g ¯ ¹. In sensory analysis, significant differences were detected in flavor tasters between the fillet matrinxã of Missioneira and the Cristalino river. Visually also no difference in coloration of the steaks was detected, and the Cristalino river with a greater tendency to salmon tones. We conclude that the provision of supplemental food changed the diet, chemical, flavor composition and color of fillets Brycon falcatus in Teles Pires rivers of the basin. Considering the high concentration of Chromium and Copper in samples of liver and muscle Brycon falcatus, we find that there is evidence of contamination by heavy metals. Nevertheless, it is necessary for the analysis of metals in water these water bodies in food items matrinxã, and other organs of matrinxã as gills, kidneys, stomach and intestines to verify the source of these contaminations.